BUILDING OF A FRAMEWORK FOR THE IMPLEMENATION OF AN INJURY PREVENTION STRATEGY: AN ALBERTA, CANADA EXAMPLE. (7th October 2012) - Belton, K; MacDonald, N; Voaklander, D
Abstract : Background: The Alberta injury death rate per 100 000 has remained unchanged from 1999 (47.1) to 2008 (48.3). The Alberta Injury Control Strategy (AICS) was developed to address this need. Aims/Objectives/Purpose: The purpose was to develop an implementation plan for the AICS. The Plan aims to accomplish results these areas: engage Albertans, to make the injury issue a priority and reduce the frequency and severity of injuries. Methods: A Steering Committee comprised of top bureaucrats from 13 ministries within the Alberta Government was created to oversee the development and execution of the implementation plan for the AICS. Results/Outcome: A framework was developed identifying actions to be taken across all ministries within the Provincial government. Three types of actions were identified. Core actions—essential actions to be taken to achieve the intended outcomes. Supporting actions—integral to all injury prevention initiatives and supporting the outcomes for each of the core actions. Promoting actions—actions that promote initiatives that are already underway. Significance/Contribution to the Field: This document provides a template for use by all stakeholders involved in injury prevention regardless of the type of injury. Although specific injury priorities are identified, it is intended that all organisations, communities and individuals will be able to identify actions they can take to reduce injuries.